A New Species of Allocreadium Looss, 1900 (Allocreadoidea: Allocreadiidae) in Wallago attu Bloch and Schneider, 1801 (Siluriformes: Siluridae) from Yamuna River at Yamuna Nagar, Haryana - Upadhyay, Sushil Kumar; B, Babita; Singh, Manoj; Yadav, Mukesh; Kumar, Vikas; Singh, Raj; Pandey, Yogendra Prasad; Nanware, Sanjay Shamrao; Sharma, Anil Kumar (Asian Journal of Biological and Life Sciences)
Background: Allocreadium Looss is a digenetic parasitic trematode of the family Allocreadiidae Stossich and is predominantly found in freshwater catfishes. There are more than 104 species of Allocreadium sp. known from a wide range of hosts including 44 Indian species so far. The selected site of the investigation was unexplored in terms of helminth diversity, therefore present investigation was designed to find out and taxonomically evaluate the trematodes population in the fish hosts. Materials and Methods: The morphological, microscopic, and morphometric assessment of the recovered endoparasitic worms was performed in the Zoology Laboratory, Department of Bio-Sciences and Technology, M.M. (Deemed to be University), from July 2018 to June 2020. The newly recovered allocreadoidean trematodes were diagnosed as a species of Allocreadium Looss (Allocreadoidea: Allocreadiidae) on the basis of the generic diagnostic charades as per the Key to the Trematoda during the present investigation from the intestine of freshwater catfish Wallago attu Bloch and Schneider (Siluriformes: Siluridae) of river Yamuna at Yamuna Nagar (Haryana), India. Conclusion: The morphotaxometric analysis of the present worms with the prior detailed types of similar genera through the advanced statistical tool the Polythetic divisive classificatory system reflected the striking contrasts of taxonomic significance. Therefore, based on the numerous remarkable contrasts in the blend of recognizing features of taxonomic significance, the present worms proposed to be the newer Allocreadium haryanii n.sp.
Keywords: Allocreadium haryanii n.sp.; Morphotaxometry; Morphotaxonomy; Trematodes; Wallago attu